Effects of dielectric barrier discharge cold plasma on the activity, structure and conformation of horseradish peroxidase (HRP) and on the activity of litchi peroxidase (POD). (April 2021) - Wang, Yijie; Ye, Zichong; Li, Jiahui; Zhang, Yan; Guo, Yingxi; Cheng, Jun-Hu
Abstract: Litchi is one kind of the precious tropical fruits, but it is easily affected by enzymatic browning resulting in great loss to farmers. In the present study, dielectric barrier discharge cold plasma was used to inactivate the litchi peroxidase (POD), one of the enzymes responsible for browning. Results indicated that after 10 min treatment, the residual activity of the POD extracted from pericarp decreased to 47.16%. The effect of cold plasma on POD structure was studied by using horseradish peroxidase (HRP) as a model enzyme. The HRP activity was decreased by about 85% after 180 s of treatment. UV and fluorescence spectral results suggested that the secondary and tertiary structures of HRP were changed through plasma treatment, hydrophobic aromatic amino acids and hemes were exposed and modified. Circular dichroism (CD) spectra indicated that after exposed to plasma for 180 s, the content of α-helix in HRP were decreased from 21.41% to 8.53%, and the β-sheet content raised from 23.29% to 32.11%. The presented study concluded that cold plasma is capable of reducing the activity of litchi POD, which will provide a new thought for prolonging shelf life of easy-browning fruits. Highlights: The litchi peroxidase (POD) activity decreased after cold plasma treatment. Horseradish peroxidase (HRP) was used to study the effect on POD changes. The secondary/tertiary structures of HRP changed after cold plasma treatment. Tyr and Trp in HRP were exposed and modified after cold plasma treatment.